TRANSFERRING STUDY PROCESS INTO VIRTUAL ENVIRONMENT: WHY IS IT NEEDED? - Piscikiene, Inga; Šustickienė, Brigita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The paper presents a comparative analysis of the opinion regarding the advantages and disadvantages of virtual environment Moodle among lecturers and students in 2015 and in 2018 and correlations with increased use of Virtual Learning Environment (VLE) to improved study outcomes. The study has revealed that virtual learning environments are beneficial for the study process as they create new learning opportunities, increase access to learning material and allow time and space flexibility. The purpose of this study is to examine the use of Moodle in a college type higher education institution in 2018 and compare the results of the survey to those obtained in a similar survey in 2015 in the same college, as well as relating the change in the use of Moodle to the change in the study outcomes. The interviewees were the lecturers and students who answered questions related to the use of Moodle. The implemented learning environment includes 14 feature creation functions and 7 resources. The evaluation results indicate that Moodle is commonly used to deliver course content, develop a course plan, evaluate, create activities, and communicate with course participants. Among many functions offered by Moodle only some of them are considered to be very important and commonly used, such as tasks, reviews, tests and workshops.